Peg Shaped Permanent Mandibular Central Incisor - A Case Report - K N Zameera; Balaji Rao; L Ashok (Wolters Kluwer Medknow Publications, 2004)
A rare case of peg shaped, permanent mandibular central incisor is presented. A female patient being a receptionist by occupation was upset regarding her unpleasant smile and desired for appropriate treatment. The tooth had a typical morphology suggesting a peg shaped incisor. Conservative treatment was advised and a "Smile worth a million dollars" was obtained.